2005
DOI: 10.1152/ajpgi.00536.2004
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of intracellular histamine H2receptor cycling precedes antagonist-induced upregulation

Abstract: Long-term administration of a histamine H2 receptor (H2R) antagonist (inverse agonist) induces upregulation of H2R in parietal cells, which may be relevant to the rebound hypersecretion of gastric acid that occurs after withdrawal of treatment. The mechanisms underlying this effect are unknown. We hypothesized that the H2R upregulation could be related to receptor trafficking and used H2R-green fluorescent protein (H2R-GFP) to test the hypothesis. Human H2R-GFP was generated and functionally expressed in HEK-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…Next, we further examined whether the cytosolic release of 3D8 scFv from caveolae/caveosome re- quires the fusion with early endosomes and late endosomes, or lysosomes. As uptake by caveosomes is a slower process than that by clathrin-coated pits [30], HeLa cells were incubated with 3D8 scFv for 2 h or transferrin for 30 min before being fixed and then fluorescently labeled with Abs against 3D8 scFv and EEA-1 (early endosomal antigen-1) or lysotrackerred, agent accumulated in late endosomes/lysosomes [31]. The resulting overlays revealed that the signal of 3D8 scFv merged with only that of cav-1, but not with EEA-1 and lysotracker-red, whereas transferrin that is delivered to early and/or late endosomes before being recycled to plasma membrane was colocalized with EEA-1 and lysotracker-red, but not with cav-1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we further examined whether the cytosolic release of 3D8 scFv from caveolae/caveosome re- quires the fusion with early endosomes and late endosomes, or lysosomes. As uptake by caveosomes is a slower process than that by clathrin-coated pits [30], HeLa cells were incubated with 3D8 scFv for 2 h or transferrin for 30 min before being fixed and then fluorescently labeled with Abs against 3D8 scFv and EEA-1 (early endosomal antigen-1) or lysotrackerred, agent accumulated in late endosomes/lysosomes [31]. The resulting overlays revealed that the signal of 3D8 scFv merged with only that of cav-1, but not with EEA-1 and lysotracker-red, whereas transferrin that is delivered to early and/or late endosomes before being recycled to plasma membrane was colocalized with EEA-1 and lysotracker-red, but not with cav-1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, inverse agonists may require chronic administration and therefore exert some undesirable effects. For instance, receptor up-regulation could occur as it was observed for the H 2 receptor after long-term treatment with cimetidine or ranitidine (Osawa et al, 2005;Smit et al, 1996), providing a plausible explanation for the tolerance to these inverse agonists after prolonged clinical use. In the same way, Milligan and colleagues showed that inverse agonists also up-regulate ȕ 2 -and Į 1B -ARs (Georgieva et al, 2008;Lee et al, 1997;MacEwan and Milligan, 1996).…”
Section: Potential Clinical Uses Of Inverse Agonists Of the Histaminementioning
confidence: 86%
“…They suggested that this observation reflected an increase in receptor number (or upregulation). Upregulation is believed to relate to suppression of H 2 receptor degradation and the recycling of H 2 receptors .…”
Section: Discussionmentioning
confidence: 99%